Study of jet shapes in inclusive jet production in pp̄ collisions at s=1.96 TeV - Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2005)
We report on a study of jet shapes in inclusive jet production in pp̄ collisions at s=1.96 TeV using the upgraded collider detector at Fermilab in Run II (CDF II) and based on an integrated luminosity of 170 pb-1. Measurements are carried out on jets with rapidity 0.1<|Yjet|<0.7 and transverse momentum 37GeV/c